2021
DOI: 10.1186/s12284-021-00456-1
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel QTLs for the Harvest Index that Contribute to High-Yield Production in Rice (Oryza sativa L.)

Abstract: Background The harvest index (HI) is a measure of the biological success of forming harvestable products. However, our understanding of the genetic basis of HI in rice (Oryza sativa L.) is limited, because it is a complex trait consisting of various yield-related traits and physiological attributes. YTH183 is a high-yielding line with large panicles and high HI derived from a cross between the Indica Group variety IR 64 and the NPT line IR 69093-41-2-3-2 (YP5). Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[27] recorded that Si did not influence the 1000-grain weight, which is aligned to this experiment. GHI is a complex characteristic comprised of several yield-related traits and physiological properties [56], could be the reason for the insignificant result on GHI in this study. Moreover, there are some other factors which can contribute to this phenomenon; nutrient availability, water availability, temperature and grain quality may have a greater impact on GY, which is considered as a crucial factor for determining GHI.…”
Section: Growth and Yield Parametersmentioning
confidence: 68%
“…[27] recorded that Si did not influence the 1000-grain weight, which is aligned to this experiment. GHI is a complex characteristic comprised of several yield-related traits and physiological properties [56], could be the reason for the insignificant result on GHI in this study. Moreover, there are some other factors which can contribute to this phenomenon; nutrient availability, water availability, temperature and grain quality may have a greater impact on GY, which is considered as a crucial factor for determining GHI.…”
Section: Growth and Yield Parametersmentioning
confidence: 68%
“…Similarly, several studies found that mild water stress has little impact on rice plant height, while severe water stress significantly reduces rice plant height [21][22][23]. Other research revealed that when the soil moisture content reached 90% of the field capacity, rice yield was the highest [24,25]. This demonstrates that appropriate irrigation plays a key role in rice growth and development.…”
Section: Discussionmentioning
confidence: 89%
“…Harvest index, number of productive tillers, number of maximum tillers, grain dry weight per panicle, number of filled grains and number of empty grains in rice are affected by genetic, environment and genetic-environment interactions. Saito et al (2021) found two novel QTLs (quantitative trait loci) controlling harvest index in rice. Harvest index is also affected by Phosphorous and Zinc concentration (Amanullah and Imanullah, 2016).…”
Section: Evaluation Of Agronomic Characteristics Of Transgenic Ricementioning
confidence: 99%